Conceptualising COVID-19’s impacts on household food security - Devereux, Stephen; Béné, Christophe; Hoddinott, John F. (Springer, 2020)
COVID-19 undermines food security both directly, by disrupting food systems, and indirectly, through the impacts of lockdowns on household incomes and physical access to food. COVID-19 and responses to the pandemic could undermine food production, processing and marketing, but the most concerning impacts are on the demand-side – economic and physical access to food. This paper identifies three complementary frameworks that can contribute to understanding these effects, which are expected to persist into the post-pandemic phase, after lockdowns are lifted. FAO’s ‘four pillars’– availability, access, stability and utilisation – and the ‘food systems’ approach both provide holistic frameworks for analysing food security. Sen’s ‘entitlement’ approach is useful for disaggregating demand-side effects on household production-, labour-, trade- and transfer-based entitlements to food. Drawing on the strengths of each of these frameworks can enhance the understanding of the pandemic’s impacts on food security, while also pinpointing areas for governments and other actors to intervene in the food system, to protect the food security of households left vulnerable by COVID-19 and public responses.